Sea Urchin Removal as a Tool for Macroalgal Restoration: A Review on Removing “the Spiny Enemies” - Miller, Kelsey I.; Blain, Caitlin O.; Shears, Nick T. (Frontiers in Marine Science, 2022)
Kelp and macroalgal forests provide the ecological foundations of many temperate rocky reef ecosystems, but have regionally declined, often due to sea urchin overgrazing and the formation of urchin barrens. Sea urchin removal has long been used to investigate kelp-sea urchin dynamics and is increasingly being promoted for kelp forest restoration. In this review, we assess the methods and outcomes of sea urchin removal experiments to evaluate their potential use and feasibility as a tool for restoring macroalgal forests. Seventy-nine sea urchin removal projects were reviewed from temperate subtidal rocky reef systems between 1975 and 2020. Removal methods were often not reported (35%), but included manual culling, including crushing (25%) and chemical application (quicklime, 9%), or relocating sea urchins (13%). Only a small percentage of removals were large in scale (16% > 10 ha) and 92% of these utilized culling. Culling is often the most practical method of urchin removal, but all methods can be effective and we encourage development of new approaches that harvest and utilize low-quality urchins. Urchin removal led to an increase in macroalgae in 70% of studies, and a further 21% showed partial increases (e.g., at one or more sites or set of conditions). Restoration effectiveness is increased by removing essentially all sea urchins from discrete areas of urchin barrens. Sea urchin removal provides a simple, relatively cheap, and effective method that promotes kelp recovery within urchin barrens. However, sea urchin removal does not address the underlying cause of elevated sea urchin populations and is unlikely to provide a long-term solution to restore kelp forests and full ecosystem function on its own. We therefore suggest that if sea urchin removal is considered as a tool for kelp forest restoration, it should be incorporated with other management measures that aim to increase kelp forest resilience and biodiversity (e.g., marine protected areas, predator protection or enhancement). This will ensure that kelp restoration efforts have the greatest ecological, socio-economic and cultural outcomes in the long-term.